DIEAP Flap Patients Equally as Satisfied with the Abdomen as Abdominoplasty Patients - Christoffer Aam Ingvaldsen, MD; Tyge Tind Tindholdt, MD, PhD; Kim Alexander Tønseth, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. The dermolipectomy of the deep inferior epigastric artery perforator (DIEAP) flap procedure is designed to give an end result as seen with abdominoplasty (AP). Several steps of an AP are, however, not routinely performed. This study compared the patient-reported outcomes between these 2 procedures with an emphasis on the abdomen. Methods:. Thirty-four patients reconstructed with a DIEAP flap (DIEAP group), and 30 patients with an AP (AP group) were asked to complete 2 study-specific questionnaires. The first questionnaire covered abdominal outcomes, whereas the second was concerned with general outcomes. Results:. The DIEAP group was significantly older compared with the AP group. Eighty-five percentage of the DIEAP group and 66 % of the AP group answered the questionnaires. Postoperatively, the DIEAP group was significantly more satisfied with their bodies when dressed (P = 0.009), and there was a trend of DIEAP patients being more satisfied with the appearance of the abdomen (P = 0.085). No significant difference was found comparing outcomes concerning umbilicus, muscle function, pain, scarring, and contour. The DIEAP group was more worried about their health than the AP group postoperatively (P = 0.044). AP patients had a significantly more altered body image (P = 0.016) and increased sexual desire (P = 0.003) than DIEAP patients. There was no significant difference regarding changes in self-image, social relationships, being naked with partner, and overall satisfaction. Conclusion:. DIEAP flap patients were equally as satisfied with the abdomen as AP patients.